Practicing ethical research to empower sexual assault survivors in higher education: An international perspective - Amber L. Giffin; Mitsunori Misawa (Adult Education Research Conference, 2021)
Sexual violence is a major global health concern and sociocultural issue (World Health Organization, 2021), with around one-third of sexual assault survivors developing mental health issues (Carey et al., 2018). However, there is a dearth in research about sexual assault survivors in higher education. Therefore, this paper will explore how researchers can ethically empower sexual assault survivors through research processes in higher education. The questions guiding this study are: 1) What are the current strategies used by researchers to ethically empower sexual assault survivors in higher education? 2) How do researchers employ these strategies in practice?
Keywords: sexual assault; higher education; research practices; ethical research; empowerment